Analysis of collocational word combinations in the exercises of the textbooks Netzwerk Neu A2 & B1 - Lestari, Fitria Legiana; Chaiwan, Patcharin (Nexus Publishing, 2024)
This thesis investigates how the textbooks Netzwerk Neu A2 & B1 support teaching collocations in German as a Foreign Language in Indonesia. It categorizes collocation exercises, qualitatively analyzing them following Gevkalyuk (2009), Stojić (2016), and Targońska and Stork (2017). Exercises are compared across A2 and B1 levels. Netzwerk Neu A2 & B1 offers numerous collocation exercises, primarily in the workbooks rather than in the coursebooks, with A2 exercises slightly outnumbering B1. Most focus on receptive skills, necessitating a balanced approach including both receptive and productive skills. German teachers in Indonesia play a crucial role, designing effective teaching methods and emphasizing collocation benefits and importance. The proposed teaching model for A2 and B1 enables parallel development of receptive and productive collocation skills. This research provides valuable insights for German language educators, offering a practical approach to enhancing collocational competence among learners. Through meticulous analysis and comparison, this thesis contributes to optimizing collocation teaching strategies, benefiting both teachers and learners in the Indonesian context.